2009
DOI: 10.2527/jas.2008-1411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary crude protein and supplemental urea levels on nitrogen and phosphorus utilization by feedlot cattle1

Abstract: Three dietary CP concentrations (11.5, 13.0, and 14.5% of DM) and 3 supplemental urea levels (100, 50, and 0% of supplemental N) were used in a completely randomized block design experiment conducted at 2 locations to determine N and P balance and serum urea N (SUN) concentrations of feedlot cattle. Crossbred steers [British and British x Continental; initial BW = 315.0 +/- 3.2 kg at location 1 (n = 27) and initial BW = 353.2 +/- 8.4 kg at location 2 (n = 27)] were used in 3 nutrient balance sampling periods (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
6
38
2
Order By: Relevance
“…This concentration is lower than values measured in feedlot cattle provided corn-based diets containing between 10 and 14% CP Walker et al 2006;Vasconcelos et al 2009) and reflects the relatively low N content of diets fed in the present experiment. Johnson and Preston (1995) suggested that optimal N utilization will be observed at plasma urea-N concentrations between 5 and 8 mg 100 mL (1 .…”
Section: Plasma Urea and Amino Acidscontrasting
confidence: 62%
See 1 more Smart Citation
“…This concentration is lower than values measured in feedlot cattle provided corn-based diets containing between 10 and 14% CP Walker et al 2006;Vasconcelos et al 2009) and reflects the relatively low N content of diets fed in the present experiment. Johnson and Preston (1995) suggested that optimal N utilization will be observed at plasma urea-N concentrations between 5 and 8 mg 100 mL (1 .…”
Section: Plasma Urea and Amino Acidscontrasting
confidence: 62%
“…This type of diet, however, may cause subacute ruminal acidosis and result in health problems (Fulton et al 1979;Bevans et al 2005). Excess protein supply will also contribute to undesirable release of N in the environment (Guo et al 2004;Vasconcelos et al 2009). …”
mentioning
confidence: 99%
“…It is unclear how these changes in total tract digestibility were partitioned within the gastrointestinal tract, although the soybean meal effect described earlier would be expected to exert its effect ruminally. The increase in N retention for 12.1% CP diets may be explained by the increase in nutrient availability owing to increased diet digestibility, resulting in increased energy and protein available for protein deposition at the tissue level (Greathouse et al 1974;Ludden et al 2002;Vasconcelos et al 2009). Other authors have also reported increased N retention and urinary N excretion with increasing N intake (Archibeque et al 2002;Wickersham et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its low cost per unit of nitrogen (N) compared with most sources of natural protein, urea (U) is typically the primary source of supplemental N in conventional steam-flaked corn-based finishing feedlot diets (Vasconcelos et al 2009). Previous reports (Milton et al 1997;Zinn et al 2003) have shown that supplemental U has more positive effects on growth performance or dietary energy utilization when the diet contains a starch:acid detergent fibre (S:ADF) ratio of greater than 5.0.…”
Section: Introductionmentioning
confidence: 99%